Analisis Komparatif Algoritma Cipher Hill, Cipher Vigenère, dan Cipher Caesar pada Proses Enkripsi dan Dekripsi Data Teks - Yunita Septriana Anwar; Rizki Azis Al Kautsar (Mandalika Mathematics and Educations Journal, 2026)
Classical cryptography is one of the information security methods that employs message transformation techniques to preserve data confidentiality. Several widely used classical cryptographic algorithms are the Caesar Cipher, Vigenère Cipher, and Hill Cipher, each of which has distinct encryption mechanisms and security levels. This study aims to analyze the characteristics, advantages, and limitations of these three algorithms and to compare their encryption and decryption processes. The results indicate that the Caesar Cipher is the simplest and easiest algorithm to implement; however, it provides a low level of security due to its vulnerability to frequency analysis attacks. The Vigenère Cipher offers a higher level of security through its polyalphabetic substitution mechanism, although it remains susceptible to cryptanalysis when the key pattern and length can be estimated. The Hill Cipher provides an even higher level of security by employing polygraphic substitution based on matrix operations, resulting in better diffusion and a larger key space. Nevertheless, its implementation is relatively more complex and requires the use of a key matrix that is invertible modulo a given integer.